PERAN KOMUNIKASI UNTUK MENGURANGI TINGKAT RETUR PADA PEMBELIAN SPARE PARTS DI PT. WIRA BHUMI SEJATI - Sri Wahyuni Yuni (Media Mahardhika, 2023)
Communication within the organization plays an important role in conveying information. PT. Wira Bhumi Sejati is a general contractor company located in Surabaya, East Java, which has several own mines and offers heavy equipment rental services. The problem discussed in this article is heavy equipment spare parts that often return because they are not suitable or not suitable, on this basis the researcher intends to examine this problem. Data analysis used descriptive qualitative methods, the research subjects were divisions related to the purchase of spare parts. The data collection technique used primary data from interviews and observations. The results of the study (1) communication plays an important role in the purchase of spare parts in the form of internal and external communication (2) the cause of frequent returns is because most suppliers of PT. Wira Bhumi Sejati is a local supplier where they do not have an IT system for tracking the part number of spare parts requested, this triggers returns (3) the solution given to reduce the return rate is to choose an official supplier.